The chemistry of the intervertebral disc in relation to its physiological function and requirements - Urban, J; Maroudas, A (1980)
The author has shown in this chapter that whilst at the moment there is still a considerable shortage of experimental data relating to the chemical and physical properties of the intervertebral disc, the broad physicochemical principles underlying its physiology are now fairly clear. It particular, it should become possible in the future to describe the nutrition of the intervertebral disc and its mechanical behavior in terms of the basic structure of the tissue and the well defined physicochemical properties of its components.